2020
DOI: 10.3390/rs13010041
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Cropland Trends and Their Nexus with Agrometeorological Parameters in the Indus River Plain

Abstract: The fine-scale insights of existing cropland trends and their nexus with agrometeorological parameters are of paramount importance in assessing future food security risks and analyzing adaptation options under climate change. This study has analyzed the seasonal cropland trends in the Indus River Plain (IRP), using multi-year remote sensing data. A combination of Sen’s slope estimator and Mann–Kendall test was used to quantify the existing cropland trends. A correlation analysis between enhanced vegetation ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…The results revealed significant positive trends of the NDVI at seasonal temporal scale and spatially at basin as well as grid scale. Previous investigations on vegetation dynamics covering parts of our study area identified comparable greening trends (Chen et al, 2019;Lamchin et al, 2018;Sarmah et al, 2018;Zhou and Ismaeel, 2020). Our results additionally reveal spatial patterns of seasonal trends and trends differentiated by land cover and land use classes at basin scale until the end of 2020.…”
Section: Discussionsupporting
confidence: 83%
“…The results revealed significant positive trends of the NDVI at seasonal temporal scale and spatially at basin as well as grid scale. Previous investigations on vegetation dynamics covering parts of our study area identified comparable greening trends (Chen et al, 2019;Lamchin et al, 2018;Sarmah et al, 2018;Zhou and Ismaeel, 2020). Our results additionally reveal spatial patterns of seasonal trends and trends differentiated by land cover and land use classes at basin scale until the end of 2020.…”
Section: Discussionsupporting
confidence: 83%
“…The results revealed significant positive trends for the NDVI at annual and seasonal temporal scale as well as spatially at basin and grid scale. Previous investigations on vegetation trends covering parts of the investigated study area identified comparable greening trends (Chen et al, 2019;Lamchin et al, 2018;Sarmah et al, 2018;Zhou and Ismaeel, 2020). Based on the multi-faceted trend analyses of this study, it was shown that irrigated and rainfed croplands significantly contributed to vegetation greening (Table 3).…”
Section: Direct Controlssupporting
confidence: 68%
“…One widely used method for trend analysis is the Mann-Kendall (MK) test, which is a nonparametric statistical test that assesses the presence of monotonic trends in time series data (Zheng et al, 2021). This test has been applied in various studies to analyze trends in different climatic and hydrological variables, including yield losses, streamflow, climatic records, snowpack accumulation, cropland trends, precipitation, groundwater levels, and evapotranspiration (Helsel and Frans, 2006;New et al, 2006;Harpold et al, 2012;Shephard et al, 2014;Yeh et al, 2015;Palizdan et al, 2017;Chang et al, 2018;Djaman et al, 2018;Ali et al, 2019;Fang et al, 2019;Tayyab et al, 2019;Mirdashtvan and Mohseni Saravi, 2020;Patakamuri et al, 2020;Avino et al, 2021;Hu et al, 2021;Zheng et al, 2021;Zhou and Ismaeel, 2021;Nkiaka, 2022;Paudel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%